2005
DOI: 10.1248/cpb.53.225
|View full text |Cite
|
Sign up to set email alerts
|

New Phenolic Glycosides from the Seeds of Cucurbita moschata

Abstract: Pumpkin, the fruits of Cucurbita moschata (Cucurbitaceae), has been used as a popular vegetable in cooking since antiquity and the pumpkin seeds are utilized in several countries as snacks after salting and roasting. The pumpkin seeds are also an important Traditional Chinese Medicine in the treatment of cestodiasis, ascariasis, and schistosomiasis. 1)Pharmacological studies on the seeds have demonstrated hepatoprotective 2) and antitumor activities.3) To our knowledge, most of the chemical studies on pumpkin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…However, the presence of antinutrients in pumpkin seeds which have been shown to have detrimental physiological effects on growing rats and chicks limits its nutritional value and hence limits the usefulness of fresh pumpkin seed as a protein source for human food [31][32][33]. Several phytochemicals such as polysaccharides, phenolic glycosides, 13-hydroxy-9Z, 11E-octadecatrienoic acid from the leaves of pumpkin, proteins from germinated seeds, have been isolated [34][35][36][37][38].…”
Section: Phytochemistry and Technologymentioning
confidence: 99%
“…However, the presence of antinutrients in pumpkin seeds which have been shown to have detrimental physiological effects on growing rats and chicks limits its nutritional value and hence limits the usefulness of fresh pumpkin seed as a protein source for human food [31][32][33]. Several phytochemicals such as polysaccharides, phenolic glycosides, 13-hydroxy-9Z, 11E-octadecatrienoic acid from the leaves of pumpkin, proteins from germinated seeds, have been isolated [34][35][36][37][38].…”
Section: Phytochemistry and Technologymentioning
confidence: 99%
“…Traditionally, the nutrition quality factor comprises major nutrients such as carbohydrates, fats and proteins, as well as minor components such as minerals, vitamins, fibers (Bourne, 2002) and the well studied phenolics or not extensively studied various others (Jiang & Du, 2011;Koike, Li, Liu, Hata, & Nikaido, 2005;Li et al, 2009) or still unidentified minor food compounds. In the last decades many studies have revealed that minor food components such as various lipids (Demopoulos, Karantonis, & Antonopoulou, 2003;Fragopoulou, Demopoulos, & Antonopoulou, 2009;Nasopoulou, Karantonis, Detopoulou, Demopoulos, & Zabetakis, 2014) and phenolics (Del Rio et al, 2013) exert beneficial effects in human health by preventing chronic disease development in humans such as cardiovascular diseases and diabetes type II.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides, proteins and peptides, para-aminobenzoic acid, and sterols are biologically active components, which are contained within pumpkins (Appendino, Jakupovic, Belloro, & Marchesini, 1999;Kuhlmann, Koetter, & Theurer, 1999). The leaves of pumpkins contain phytochemicals such as phenolic glycosides, 13-hydroxy-9Z, 11E-octadecatrienoic acid, in addition to proteins from germinated seeds (Bang et al, 2002;Koike, Li, Liu, Hata, & Nikaido, 2005). Much research has been written on the medicinal activities of these polysaccharides and proteins such as: 1) antibacterial (Hammer, Carson, & Riley, 1999); 2) hypocholesterolaemic and antioxidant (Kong, 2000); 3) immunomodulatory (Xu, 2000); 4) antimutagenic (Ito, Maeda, & Sugiyama, 1986); 5) anthelmintic (Diaz Obregon, Lloja, Lozano, & Carbajal Zuniga, 2004) and 6) anticancer properties (Xie, 2004).…”
Section: Introductionmentioning
confidence: 99%